Analisis Pola Kunjungan pada Objek Wisata Kabupaten Simalungun Dengan Menggunakan Algoritma Apriori Berbasis Website - Erika Purba; Andy Paul Harianja (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
Tourist attractions are places of interest and visited by tourists because they have certain appeals. These attractions can include natural tourism, cultural tourism, artificial tourism, or agro-tourism. Simalungun Regency offers various interesting tourist spots, ranging from natural beauty such as waterfalls and lakes to rich traditional cultures that reflect local history and customs. However, information about tourist visit patterns remains limited. A deeper understanding of these patterns is crucial, especially for tourism managers in designing effective and sustainable development strategies. Therefore, this study aims to identify associations or relationships between tourist attractions based on tourist visit data. The Apriori algorithm was chosen for its ability to discover high-frequency patterns in large datasets. These patterns are expected to provide valuable insights for tourism managers in designing effective promotional strategies. Apriori is a well-known algorithm in data mining, particularly for finding frequent itemsets using association rule techniques. The algorithm is carried out by determining frequent itemsets, from 1-itemset to multi-itemsets, until the association rules are derived from the pre-selected data. To obtain these frequent itemsets, each selected data must meet the minimum support and minimum confidence requirements so that the resulting association rules are relevant and practically applicable.